2013
DOI: 10.1371/journal.pone.0064174
|View full text |Cite
|
Sign up to set email alerts
|

Discharge Competence and Pattern Formation in Peatlands: A Meta-Ecosystem Model of the Everglades Ridge-Slough Landscape

Abstract: Regular landscape patterning arises from spatially-dependent feedbacks, and can undergo catastrophic loss in response to changing landscape drivers. The central Everglades (Florida, USA) historically exhibited regular, linear, flow-parallel orientation of high-elevation sawgrass ridges and low-elevation sloughs that has degraded due to hydrologic modification. In this study, we use a meta-ecosystem approach to model a mechanism for the establishment, persistence, and loss of this landscape. The discharge compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(74 citation statements)
references
References 88 publications
(153 reference statements)
2
71
1
Order By: Relevance
“…Kaplan et al (2012) demonstrated this feedback with a hydrodynamic model of surface water flow across randomly generated patterned landscapes of varying anisotropy, finding that hydroperiod decreased exponentially with increasing patch anisotropy. Using a patchscale analytical model, Heffernan et al (2013) demonstrated strong feedbacks between the soil elevation at any given location and an adjacent location perpendicular to flow, but no such feedback parallel to flow, lending support to the central mechanism of the SOC hypothesis. However, that analytical model was limited to two patches, where flow in one cell was directly controlled by flow in the only other cell.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Kaplan et al (2012) demonstrated this feedback with a hydrodynamic model of surface water flow across randomly generated patterned landscapes of varying anisotropy, finding that hydroperiod decreased exponentially with increasing patch anisotropy. Using a patchscale analytical model, Heffernan et al (2013) demonstrated strong feedbacks between the soil elevation at any given location and an adjacent location perpendicular to flow, but no such feedback parallel to flow, lending support to the central mechanism of the SOC hypothesis. However, that analytical model was limited to two patches, where flow in one cell was directly controlled by flow in the only other cell.…”
Section: Introductionmentioning
confidence: 80%
“…Although multiple hypotheses exist for explaining the ridge-slough pattern, most of them attribute the development of these landscapes to one dominant process. The self-organizing-canal hypothesis (Cohen et al, 2011;Heffernan et al, 2013), on the other hand, ascribes pattern formation and maintenance to reciprocal feedbacks between landscape pattern and hydrology. Moreover, evidence of a strong feedback between pattern and hydroperiod (Kaplan et al, 2012) lends support for the SOC.…”
Section: Testing the Self-organizing-canal Hypothesismentioning
confidence: 99%
See 3 more Smart Citations